(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Polycystic ovary syndrome (PCOS) is the most common cause of chronic anovulation and hyperandrogenism in young women. This syndrome is characterized by an increase in the number of small antral follicles that are between 5-8 mm in size. Antemüllerian hormone (AMH) is secreted mostly by this type of follicle and when it is much too high, the production of a healthy egg every cycle can be halted as it works by reducing the receptors of the ovary to follicle stimulating hormone (FSH). Objective: To compare the AMH level between women presented with PCOS with its level in normal ovulatory infertile women and to determine its correlation with the clinical, hormonal and ultrasonographic parameters in both groups. Methods: This is a prospective cross-sectional study done at Um-Albaneen Infertility Center in Al-Imamein Al-Kadhimein Medical City from march 2015 to January 2016. One hundred infertile women were recruited in this study, 50 women with PCOS and 50 women have other factors of infertility apart from PCOS and ovulatory dysfunction. Sera were taken from all the participants at day (2-3) of menstrual cycle and were investigated for AMH, FSH, luteinizing hormone (LH), androstenedione, testosterone and estradiol (E2) levels. The number of early antral follicles (2-9 mm in diameter) was estimated by transvaginal ultrasound scanning. Results: Level was significantly higher in PCOS women (42.6±23.8) compared to the normal ovulatory infertile women (16±7.5), P-value